Interprofessional Competence of Health and Social Care Professionals Working in Specialized Palliative Care: A Cross‐Sectional Study - Kesonen, Pauliina; Salminen, Leena; Soikkeli‐Jalonen, Anu; Saarinen‐Nassar, Johanna; Haavisto, Elina (Wiley, 2026)
Aim
The aim of this paper is to assess interprofessional competence and explain factors associated with it among health and social care professionals working in specialized palliative care hospital wards.
Design
The research study employs a descriptive cross-sectional approach.
Ethics
The study followed good scientific practice. Ethical approvals were obtained from the Ethics Committee of Tampere University (85/2022) and the Ethics Committee of the Pirkanmaa Wellbeing Services County (6/2023). Research permits were obtained separately from each institution that participated in the study. Participation was voluntary, contingent on informed consent and the confidentiality of participants was protected.
Methods
In total, 153 health and social care professionals from 16 specialized palliative care wards in Finland participated in the study. The data were collected from May 2023 to March 2024, using the previously validated generic IPEC instrument and newly developed, palliative-care-specific ICOPA self-assessment instruments. Data were analysed using descriptive and inferential statistics. Due to the data not being normally distributed, non-parametric Mann–Whitney U and Kruskal–Wallis tests were applied, depending on the number of groups compared. Pearson's correlation was used to examine associations between variables.
Results
Health and social care professionals self-assessed their interprofessional competence as good. Among the interprofessional competencies, values and ethics were assessed highest, while teams and teamwork were assessed lowest. Education level, participation in interprofessional education, work experience, amount of teamwork conducted in their own unit, and evaluation considering teamwork functionality had a statistically significant association with professionals' better self-assessed interprofessional competence.
Conclusion
The results have identified competence gaps that will guide the development of interprofessional practice. However, because the currently used instruments are based on self-assessment, objective measures are also needed to ensure a comprehensive evaluation of interprofessional competence.